Pemanfaatan Dashboard KPI dan Analisis Data Konsumen dalam Peningkatan Strategi Pemasaran dan Pelayanan di Terminal Bus Serang - Arfiani Yulianti Fiyul; Siti Maspupah; Tjetjep Sudrajat; Aditya Bayu Azi (CV. ITTC INDONESIA, 2025)
This study discusses the use of KPI dashboards and consumer data analysis to improve marketing strategies and service quality at the Serang Bus Terminal. The research approach is combinatory: contextual, reviewing literature related to marketing analysis, KPIs, and dashboards; and application, collecting primary and secondary data, including observations of terminal operations, passenger satisfaction monitoring, and analysis of transaction/visit data (simulative). The study results indicate that designing a KPI dashboard integrated with key service indicators (e.g., schedule punctuality, customer satisfaction, waiting time, and seat occupancy) can accelerate data-driven decision-making and improve marketing campaign effectiveness and service quality. Practical recommendations include developing a simple BI system (e.g., Power BI or Tableau), prioritizing KPIs, integrating data across functions (operations, marketing, and service), and training terminal managers to build a culture of data-driven decision-making. These findings are relevant for terminal managers, transportation agencies, and researchers in the marketing and transportation fields.